Karakteristik Kimia dan Sensori Kulit Pai Berbahan Tepung Komposit Bonggol Pisang dan Sukun - Riftyan, Emma; Nisbah, Nisbah; Fitriani, Shanti (Program Studi Teknologi Pangan, 2024)
Pie is a a type of pastry that consists of pie crust dough and filling. The texture of a well-made pie crust is arid and coarse. The texture of pie crust can be affected by the use of flour with a low gluten content. This study made a pie crust using a banana hump and breadfruit composite flour. The aim of this research was to obtain the optimum ratio banana hump and breadfruit flour on the quality characteristics of crust pie. The research method used a completely randomized design (CRD) with five treatments and four replications to obtain 16 experimental units. The treatments consisted of ratio banana hump and breadfruits flour BS1 (100:0), BS2 (75:25), BS3 (50:50), BS4 (25:75), and BS5 (0:100). Parameters observed included moisture content, ash, fat, protein, carbohydrate, crude fiber, and sensory assessment (descriptive and hedonic). Data obtained were statistically analyzed using Analysis of Variance (ANOVA) and continued with Duncanâ€™s Multiple Range Test (DMRT) at a 5% level. Â The results showed significant moisture content, ash, fat, protein, carbohydrate, crude fiber, and sensory assessment. The treatments was BS4 where moisture 8.05%, ash 2.66%, fat 15.07%, protein 1.56%, crude fiber 5.21%, and carbohydrate 72.67%. The panellistâ€™s favoured the overall sensory assessment of BS4, which had a yellow colour and a slightly breadfruit flavour